Strategy Analysis of the Modern Mosque of Kurir Langit in Campaigning the Donation Movement in Parepare - Firman Syamsuddin; Iskandar; Nurhikmah; Ramli; Sumarni Sumai (Al-Iftah: Journal of Islamic studies and society, 2025)
This study aims to analyze the da'wah strategies implemented by the Modern Mosque of Kurir Langit in campaigning the Food Donation Movement in Parepare City, as well as to identify internal and external strategic factors that influence the sustainability of the program. This research employs a qualitative descriptive approach within a field research framework, involving interviews and observations with administrators, Kurir Langit volunteers, donors, and beneficiaries. Secondary data were also obtained from books, journal articles, and online sources relevant to the topic. The data analysis process followed the stages of data collection, data reduction, data presentation, and conclusion drawing. The findings show that the mosque utilizes several strategic approaches, including the use of social media flyers and short videos as campaign tools and accountability media for donors and partners. The rational approach (al-manhaj al-‘aqli) is reflected in conveying theological, social, and humanitarian benefits of donating food, while the sensory approach (al-manhaj al-hissy) appears in volunteer engagement and millennial involvement through direct humanitarian activities. The study also identifies several weaknesses, such as limited human resources, inadequate donor participation, and the mosque’s geographically distant location from the urban center. Meanwhile, opportunities arise from technological developments, improved mosque infrastructure, and strong community trust. The threats include limited time for direct socialization, challenges in food distribution, and the dominance of rice as the primary donated item. Based on these findings, the study recommends strengthening digital communication strategies, expanding partnerships with local institutions, diversifying donated food items, and increasing volunteer training to enhance program effectiveness and long-term sustainability.